PENGARUH SUBSTITUSI LERAK TERHADAP KUALITAS PRODUK HIGINE 3IN1 DENGAN PENAMBAHAN EKSTRAK KULIT NANAS SEBAGAI SENYAWA AKTIF - Suprianto, Yosep; Nurhayati, Siti; Sakha, Hanifah; Ayu, Natasha Viandra; Dhom, Juan Abu Dhom; Aprilliani, Fenny (Agros Journal of Agriculture Science, 2024)
Hygiene products commonly contain SLS (Sodium Lauryl Sulfate) which can trigger skin irritation or cause dandruff on the scalp. Through innovation and technological advancements, a 3-in-1 soap is planned to be studied to create a natural soap that is effective and contains natural ingredients that are beneficial for skin health. The aim of this research is to determine the physical and chemical characteristics of the 3-in-1 hygiene product based on sapindus (Sapindus rarak) and pineapple peel extract, and also to assess the potential microbial contamination in the 3-in-1 hygiene product. The research method used is the RAL (Randomized Complete Block Design) with 2 factors: sapindus concentration (A=15%, 22.5%, and 30%) and pineapple peel extract (B=9%, 18%, and 27%) with 3 replications. Testing parameters include physicochemical quality (viscosity, specific gravity, foam stability, and pH) as well as the inhibition ability against S. aureus and E. coli. The results show that variations in treatment have a significant effect on all test parameters except specific gravity. The best treatment was obtained by comparing data with SNI 4085:2017, resulting in treatment A2B2 with viscosity of 10,57±0,05de cp, specific gravity of 25.99±0.09 g/ml, foam stability of 71,27±0,25e %, and pH of 4,01±0,10c, with inhibition zone against E. coli of 5±0,00a mm and 6±1,41ab mm.